A systematic study of the genus Paragavialidium Zheng (Orthoptera: Tetrigoidea: Scelimeninae) - Deng, Weian; Zheng, Zhemin; Wei, Shizhen; Lin, Minping (Zootaxa, 2012)
Taxonomy of a tetrigid genus Paragavialidium Zheng is reviewed. A new species, P. serrimarginis Deng et Zheng, sp. nov. is described. The distribution and an updated identification key to all known species of the genus is given.